Effectiveness of the Use of Occupational Safety Equipment on Commercial Vessels in Patrol Operations of the Bitung Class 2 Coast Guard Base - Jundi, Muhammad; Masengi, Evi E.; Tarore, Steven V. (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study aims to analyze the effectiveness of the use of occupational safety equipment on merchant ships in patrol operations carried out by the Bitung Class II Coast Guard Base (PPLP). This study uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, direct observation, and documentation. The main focus of the study covers three aspects: planning, implementation, and supervision and evaluation of occupational safety equipment maintenance. The results of the study indicate that the maintenance planning system has not been documented in a standard and standard manner, only in the form of monthly reports that are prepared informally without a fixed schedule. The implementation of maintenance is generally preventive, but still depends on the initiative of ship officers and has not been integrated into the digital system. Meanwhile, supervision and evaluation are still internal, reactive, and have not produced comprehensive policy follow-ups. Five main determinant factors were found that influence the effectiveness of the maintenance system, namely completeness of documents, personnel capabilities, availability of spare parts, implementation of digital systems, and safety culture. This study recommends the implementation of a digital-based maintenance management system such as the Computerized Maintenance Management System (CMMS), preparation of standard maintenance documents, routine training for ship technicians, and strengthening of data-based supervision and evaluation systems as strategies to improve the reliability of occupational safety systems on merchant ships.